Structural and functional diversity of EF‐hand proteins: Evolutionary perspectives - Kawasaki, Hiroshi (Protein Sci, 2017)
We have classified 865 sequences of EF‐hand proteins from five proteomes into 156 subfamilies. These subfamilies were put into six groups. Evolutionary relationships among subfamilies and groups were analyzed from the inferred ancestral sequence for each subfamily. CTER, CPV, and PEF groups arose from a common EF‐lobe (pair of adjacent EF‐hands). They have two or more EF‐lobes; the relative positions of their EF‐lobes differ from each other. Comparisons of the ancestral sequences and the inferred structures of the EF‐lobes of these groups indicate that the mutual positions of EF‐lobes were established soon after divergence of an EF‐lobe for each group and before the duplication and fusion of EF‐lobe gene(s). These ancestral sequences reveal that some subfamilies in low similarity and isolated groups did not evolve from the EF‐lobe precursor, even if their conformations are similar to the canonical EF‐hand. This is an example of convergent evolution.